Rupture of uterine muscle hematoma following diagnostic amniocentesis at 18 weeks and uterine dehiscence at term - Krastiņa, Zane; Šavlovskis, Jānis; Langrate, Anna; Znotiņš, Toms (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine rupture during pregnancy is a rare complication that, like any rupture in other body organ, has a life-saving condition. However, in this case, it threatens both, the mother and the child lives and it can lead to serious complications such as asphyxia, hemorrhagic shock, perinatal hysterectomy, hypoxic ischemic encephalopathy, brain injury, and death. It is known, that most often, it develops during the third trimester of pregnancy or during labor. We report a patient who experienced uterine rupture with 2500 ml blood loss following the diagnostic amniocentesis at 16 weeks. The same patient had suture dehiscence at the site of hematoma what was revealed during the Caesarean section at 37 weeks and a healthy baby was delivered.